Reassessing Helicobacter pylori Eradication Strategies in the Era of Rising Antibiotic Resistance - Yilmaz Yildirım, Tuba; Özdoğan, Osman Cavit (Turkish Journal of Gastroenterology, 2026)
Cite this article as: Yilmaz Yildirım T, Özdoğan OC. Reassessing Helicobacter pylori eradication strategies in the era of rising antibiotic resistance. Turk J Gastroenterol. Published online February 19, 2026. doi: 10.5152/tjg.2026.25699.